Application Of Excise Tax On Certain Types Of Imported Products (Texas Journal of Agriculture and Biological Sciences, 2026)
This article examines the world experience of excise taxes, their impact on the economy, health and ecology. Based on the experience of countries such as the USA, the European Union, Turkey, Russia, South Korea and China, the results of excise taxes on tobacco, alcohol, sweet drinks, chips, fries, electronic cigarettes, pyrotechnics and expensive cars are reviewed. In addition, the importance of excise taxes in Uzbekistan, statistical data on excise taxes collected from imported products in 2023-2024 and international comparisons are presented. In particular, the volume of food products such as potato chips and fries, as well as luxury goods such as pyrotechnics, electronic cigarettes and expensive cars, the geography of imports, customs duties collected and benefits provided are analyzed. The article provides recommendations for improving excise taxes, promoting healthy eating, limiting the advertising and illegal trade of harmful products. These measures are aimed at increasing state budget revenues and forming a healthy lifestyle for the population